PENGARUH KUALITAS TERHADAP KEPUASAN KONSUMEN (Studi Kasus Rumah Potong Ayam PT. Ciomas Adisatwa, Tbk.) - Muhammad Natsir (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2015)
Influence on the quality of Customer Satisfaction (Case Study at Chicken slaughter house PT. Ciomas Adisatwa, Limited.) This study aims to determine is there any influence on the quality of customer satisfaction slaughter house PT. Ciomas, limited. The research was conducted on customers of Chicken slaughter house Ciomas, limited that have been transacting over one year. This research is a qualitative research design methods and eksplanatif (explanatory research). The amount of sample 37 customers slaughterhouse PT. Ciomas. Data were analyzed using univariate and bivariate analyzes. The results showed there was a significant relationship between the variables of the quality of customer satisfaction (p <0.01).